PENGARUH VARIASI PANJANG IMPELLER PADA POMPA AIR RUMAH TANGGA TERHADAP DEBIT DAN TEKANAN - Guntur Wicaksono, Farid; Fahrudin, A’rasy (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
Pump is a device used to increase pressure to flow fluid or something in the form of liquid from one place to another or from a low surface to a high surface. High pressure is exerted through the medium by imparting energy to the displaced fluid, converting mechanical energy to kinetic energy. The mechanical energy of the pump is used to increase the speed, pressure or height of the fluid. Therefore making a pump prototype by making different impeller lengths, whether it can affect the resulting flow discharge output or not. So that in the future we can conduct experiments to make an impeller which is more effective in producing a larger water discharge.